2021
DOI: 10.1093/plphys/kiab108
|View full text |Cite
|
Sign up to set email alerts
|

MKK4-MPK3-WRKY17-mediated salicylic acid degradation increases susceptibility to Glomerella leaf spot in apple

Abstract: Glomerella leaf spot (GLS), a fungal disease caused by Colletotrichum fructicola (C. fructicola), severely affects apple quality and yield, yet few resistance genes have been identified in apple (Malus domestica Borkh.). Here we found a transcription factor MdWRKY17 significantly induced by C. fructicola infection in the susceptible apple cultivar ‘Gala’. MdWRKY17 overexpressing transgenic ‘Gala’ plants exhibited increased susceptibility to C. fructicola, whereas MdWRKY17 RNA-interference plants showed opposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 41 publications
1
83
0
Order By: Relevance
“…In contrast to the results in Arabidopsis and N. benthamiana , MPK3 in apple (MdMPK3) has been reported to mediate a pathway leading to the susceptibility to C. fructicola (Shan et al, 2021 ). It is shown that MdMPK3 interacts with upstream kinase MdMKK4 on the plasma membrane and in the nucleus, and interacts with downstream transcription factor MdWRKY17 in the nucleus (Shan et al, 2021 ).…”
Section: Protein Kinases In Host Plantsmentioning
confidence: 83%
See 3 more Smart Citations
“…In contrast to the results in Arabidopsis and N. benthamiana , MPK3 in apple (MdMPK3) has been reported to mediate a pathway leading to the susceptibility to C. fructicola (Shan et al, 2021 ). It is shown that MdMPK3 interacts with upstream kinase MdMKK4 on the plasma membrane and in the nucleus, and interacts with downstream transcription factor MdWRKY17 in the nucleus (Shan et al, 2021 ).…”
Section: Protein Kinases In Host Plantsmentioning
confidence: 83%
“…In contrast to the results in Arabidopsis and N. benthamiana , MPK3 in apple (MdMPK3) has been reported to mediate a pathway leading to the susceptibility to C. fructicola (Shan et al, 2021 ). It is shown that MdMPK3 interacts with upstream kinase MdMKK4 on the plasma membrane and in the nucleus, and interacts with downstream transcription factor MdWRKY17 in the nucleus (Shan et al, 2021 ). In vitro kinase assays have shown that the MdMKK4-MdMPK3 cascade phosphorylates MdWRKY17; and the phosphorylation of MdWRKY17 regulates the activation of its target gene Downy Mildew Resistant 6 (MdDMR6) , which contributes to the degradation of SA (Shan et al, 2021 ).…”
Section: Protein Kinases In Host Plantsmentioning
confidence: 83%
See 2 more Smart Citations
“…Whether that regulation is direct or may occur through the participation of different molecular elements remains unclear. This indirect regulation occurs for the transcription factor from apple MdWRKY17 , which bounds to MdDMR6 promoter and induces its expression (Shan et al, 2021). Our results reinforce the role of SlS5H , also known as SlDMR6-1 , in SA metabolism.…”
Section: Discussionmentioning
confidence: 99%